PENGARUH PERAN ORANG TUA DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA SEKOLAH DASAR - Laelatul Fadilah; Muhammad Rio Ferdinand; Nur Khasanah; Dinar Pramudiya Wardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Elementary School (SD) is an important period in the formation of children's character and intellect. Elementary school students' academic achievement is an indicator of the success of the teaching and learning process. The role of parents is fundamental in improving the academic achievement of elementary school students. This article discusses the influence of the role of parents in improving the academic achievement of elementary school students, with a focus on several important points, such as creating a conducive learning environment, building good communication, being a good role model, supporting learning activities, and providing motivation and moral support. to find patterns of parental involvement in the academic achievement of elementary school students. Here, researchers use descriptive qualitative research methods because this research explores whether or not educational assessment standards are in accordance with the independent curriculum at SD Negeri Kalongan 02. From the results of observations and questionnaires parents get children used to having study routines apart from doing homework, such as re-reading material. which has been delivered at school, practice questions and read the next lesson material. The way parents teach their children to study regularly is different in each family. Some parents have a routine study pattern where children get used to doing homework assignments in the afternoon after coming home from school. In the evening, children are accustomed to correcting their work with their parents. Children are also accustomed to reading lesson material for the next day. In other families, children's study routine is used to do homework after school and in the evening they are used to discuss the results of their work with their parents and prepare the next day's lesson schedule.